An unfinished reformation: The persistence of gender-exclusive language in theology and the maintenance of a patriarchal church culture - Van Wyk, Tanya ca. 20./21. Jh. (Verbum et ecclesia, 2018)
For more than four decades, a variety of theologians from different backgrounds and different points of departure have argued that the language we use in reference to God and humanity should be inclusive of different genders and that exclusive language has harmful consequences. Yet, it persists because of, in part, the argument that inclusive language, specifically in reference to God, is forced and awkward and also because it is considered as an existential concern to only a minority. This article examines the persistence of gender-exclusive language in theology as an unfinished dimension of church reformation. This includes the language of theological imagery, metaphors, grammar, theological research, books used to teach theological students, academic papers at conferences, sermons, devotional texts, liturgies and church hymns. In reference to a justification of gender-exclusive language made by theologian Klaus Nürnberger in one of his recent (2016) publications, this article will provide an overview of the issues involved in debate about theology, language and gender in order to illustrate that exclusive language and its effects have become normalised, and therefore it is invisible. Therefore, the time has come for a status confessionis about gender-exclusive language.Intradisciplinary and/or interdisciplinary implications: This article brings theological discourse into discussion with linguistic studies, gender studies, hermeneutic studies and theological anthropology. It also explores the relationship between religion and religious language in general. It impacts systematic theological conceptions of 'God' and challenges metaphysical descriptions of God.